Hospital Image and Service Quality Are Not Able to Provide Patient Satisfaction and Loyalty Effect - Luhur Sukamuljo; Endang Ruswanti; Mus Aida (Penerbit Kemala Indonesia, 2021)
Patient loyalty to a hospital is the key to the development of the hospital. Satisfaction with perceived performance and the presence of emotional ties based on patient experience gives rise to trust over a long period of time. The ability of hospitals to provide quality services supported by a good hospital image will create patient satisfaction and impact on patient loyalty. This study aims to provide empirical evidence of the influence of hospital image and service quality on patient loyalty mediated by satisfaction. The research method used is quantitative methods with the type of causality research. Data source is primary. Unit analysis of inpatient patients. Data analysis with path analysis. The results showed that simultaneously the image of the hospital and the quality of service had a positive and significant effect on patient loyalty with patient satisfaction as intervening. Partially, service quality has a positive and significant effect on patient satisfaction, hospital image has no effect on patient satisfaction, patient satisfaction and hospital image have positive and significant effect on patient loyalty, service quality has no effect on patient loyalty, hospital image research findings do not affect patient satisfaction and service quality does not affect patient loyalty.